Minimizing Blood Loss in Spine Surgery. Issue 1 (January 2020) - Mikhail, Christopher; Pennington, Zach; Arnold, Paul M.; Brodke, Darrel S.; Chapman, Jens R.; Chutkan, Norman; Daubs, Michael D.; DeVine, John G.; Fehlings, Michael G.; Gelb, Daniel E.; Ghobrial, George M.; Harrop, James S.; et al.
Study Design: Broad narrative review. Objective: To review and summarize the current literature on guidelines, outcomes, techniques and indications surrounding multiple modalities of minimizing blood loss in spine surgery. Methods: A thorough review of peer-reviewed literature was performed on the guidelines, outcomes, techniques, and indications for multiple modalities of minimizing blood loss in spine surgery. Results: There is a large body of literature that provides a consensus on guidelines regarding the appropriate timing of discontinuation of anticoagulation, aspirin, nonsteroidal anti-inflammatory drugs (NSAIDs), and herbal supplements prior to surgery. Additionally, there is a more heterogenous discussion the utility of preoperative autologous blood donation facilitated by erythropoietin and iron supplementation for healthy patients slated for procedures with high anticipated blood loss and for whom allogeneic transfusion is likely. Intraoperative maneuvers available to minimize blood loss include positioning and maintaining normothermia. Tranexamic acid (TXA), bipolar sealer electrocautery, and topical hemostatic agents, and hypotensive anesthesia (mean arterial pressure (MAP) <65 mm Hg) should be strongly considered in cases with larger exposures and higher anticipated blood loss. There is strong level 1 evidence for the use of TXA in spine surgery as it reduces the overall blood loss and transfusion requirements. Conclusion: As the volume and complexity of spinal procedures rise, intraoperative blood loss management has become a pivotal topic of research within the field. There are many tools for minimizing blood loss in patients undergoing spine surgery. The current literature supports combining techniques to use a cost- effective multimodal approach to minimize blood loss in the perioperative period.